Seizure: An Adverse Effect of Regadenoson in Myocardial Perfusion Imaging - Sohab S. Radwan; Owen G. Schwartz (Case Reports in Cardiology)
Regadenoson is a selective adenosine 2a (A2a) receptor agonist that is used in cardiac stress testing to evaluate for ischemic heart disease and has largely replaced adenosine in the modern era. Since adenosine receptors are involved in synaptic transmission between neurons throughout the central nervous system (CNS) including the cerebral cortex, hippocampus, and other structures as well, regadenoson can lower the seizure threshold in susceptible individuals. Epileptogenic activity is an uncommon yet potentially severe adverse effect of regadenoson use, and therefore, more awareness is required in screening patients at risk and evaluating alternate ways to investigate coronary artery disease (CAD) in susceptible individuals.